Hubungan Derajat Ruptur Perineum Dengan Kejadian Infeksi Nifas Di Rsud Dr. M. Yunus Bengkulu Tahun 2012 - Sa’arfa Ayu; Epti Yorita; Kurniawati Arief; Kosma Heryati; Yuliana Lubis (Jurnal Kebidanan Manna, 2022)
The Bengkulu Capital City Mortality Rate in 2009 was recorded at 104.52 per 100,000 live births. The maternal mortality rate due to childbirth is still below the national death rate which reached 262 per 100,000 live births. One of the causes of maternal mortality is puerperal infection. Puerperal infection can be caused by perineal rupture. This study aims to determine the relationship between the degree of perineal rupture and the incidence of puerperal infection in dr. M. Yunus Hospital Bengkulu. This research is an analytic observation method with a case control design. The type of population in this study were all postpartum mothers who experienced perineal rupture at dr.M. Yunus Hospital Bengkulu in 2010-2011, totaling 1360 people with a sample of 148 people consisting of a case group, namely mothers with puerperal infection and a control group of mothers without postpartum infection taken with a random systematic technique. sampling. Comparison of case and control groups 1:1. Data were analyzed by descriptive statistics using t test with 95% confidence level (α = 0.05). The results of this study indicate that the average degree of perineal rupture in pregnant women is grade III. Almost all (90.5%) puerperal infections occurred in mothers with grade IV perineal rupture. There is a relationship between the degree of perineal rupture with puerperal infection in dr.M.Yunus Hospital Bengkulu in 2012 with a p value = 0.00 and a mean difference of 1.16. It is recommended for health workers to pay attention to nutrition in postpartum mothers so that they can increase body resistance and accelerate the wound healing process.